Incidencia de actividades artesanales de madera en la contaminación acústica en el casco urbano de Calceta - Loor Santana, Jefferson José (2017)
A study on the incidence of artisan activities of wood in the noise pollution in the urban center of the city of Calceta is presented, for which the artisan activities related to the use of the same one were determined, acoustic pollution was established in the zones To carry out these activities, for which observation visits and data collection were carried out when workers' surveys were applied, it was evident that the activities of the artisanal wood production process are sanding, cutting, polishing and painting, with a daily frequency ; Subsequently a sectorization of the areas where cabinetmakers were found, so it was zonifico to carry a better study, establishing two sectors where the sound pressure level is monitored which is an indicator of noise, using a sound level meter, digital Sper Cientific 840029 during two months of registration, in two periods of time during three daily days: morning, noon and afternoon, later the formula of Pressure Sound Level (NPS) was used, obtaining the values of 76.24 dB (A ) For sector 1 and 78.05 dB (A) for sector 2, both values exceed the permissible parameters required by the Unified Text of Secondary Environmental Legislation; In the third phase the environmental improvement plan was developed based on the environmental nonconformities of the artisanal activities found in the Leopold matrix that will serve to mitigate the incidence of diseases to workers.